2021
DOI: 10.1080/00140139.2021.1941279
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effect of multi-sensory stimulations on simulator sickness and sense of presence during HMD-mediated VR experience

Abstract: Some lines of evidence have shown that sensory input, especially related to vestibular and somatosensory stimulation, may reduce the symptoms related to simulator sickness and increase the sense of presence in VR. The present study aims at understanding how mechanical vibration and auditory stimulation can be used to improve user experience in the context of VR mediated by head-mounted displays. Four different groups comprising a total of 80 participants were tested under different conditions of sensory input … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 59 publications
1
15
0
Order By: Relevance
“…The present findings were consistent with relevant studies demonstrating the effects of VR training. Previous studies have shown that adding vibratory stimulation might improve the realism of the VR environment (Grassini et al, 2021) and to enhance the motor-learning effect (Grassini et al, 2020). Positive feedback for successful trials effectively reinforces participants' behavior (Abe et al, 2011;Nikooyan and Ahmed, 2015;Vassiliadis et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present findings were consistent with relevant studies demonstrating the effects of VR training. Previous studies have shown that adding vibratory stimulation might improve the realism of the VR environment (Grassini et al, 2021) and to enhance the motor-learning effect (Grassini et al, 2020). Positive feedback for successful trials effectively reinforces participants' behavior (Abe et al, 2011;Nikooyan and Ahmed, 2015;Vassiliadis et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In Kondo et al, the verbal information ("Left hit" or "Right hit") was shown on the screen. Based on recent reports showing that motor learning using VR was not effective under a non-realistic VR environment (Grassini et al, 2020(Grassini et al, , 2021, we introduced a new vibratory stimulation to enhance the reality of the collision.…”
Section: Introductionmentioning
confidence: 99%
“…The ride is part of the selection of rides available in a customer-oriented videogame ("Epic Roller Coaster" B4T games). Such type of VR was chosen for the ability to induce, even after short use, a high sense of presence as previously shown (see e.g., Grassini et al, 2021a;Grassini et al, 2021b). The virtual ride was set in a fictitious tropic island environment.…”
Section: Vr Scenariomentioning
confidence: 99%
“…The ride is part of the selection of rides available in a customer-oriented videogame ("Epic Roller Coaster" B4T games). Such type of VR was chosen for the ability to induce, even after short use, a high sense of presence as previously shown (see e.g., Grassini et al, 2021a;Grassini et al, 2021b). The virtual ride was set in a fictitious tropic island environment.…”
Section: Vr Scenariomentioning
confidence: 99%